STRATEGI PEMBELAJARAN BAHASA ARAB DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB SISWA KELAS VII DI SEKOLAH WARASANSART LAMMAI, THAILAND - Devi Permata Sari; Munawir Pasaribu (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This article aims to analyze the Arabic language learning strategies implemented by teachers to improve the speaking skills (maharah al-kalam) of seventh-grade students at Warasansart Lammai School in Southern Thailand, as well as to identify the factors that support and hinder their implementation. Warasansart Lammai School represents a unique sociolinguistic context, where Arabic is the third foreign language for students who use Thai and Patani Malay in their daily lives. Phonetic barriers resulting from Thai language interference, limited exposure to Arabic outside of school, and high levels of language anxiety are the main challenges faced by teachers. This study employs a descriptive qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with teachers, students, and the school principal, as well as documentation in the form of lesson plans and assessment records. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldana, which includes data condensation, data presentation, and verification of conclusions. Data validity was ensured through source triangulation and methodological triangulation. The results of the study show that teachers apply a combination of communicative (al-madkhal al-ittishali), constructivist, and audio-visual media-based strategies, as well as the creation of a language environment (bi'ah arabiyah), in an integrated manner. These strategies have proven effective in reducing speaking anxiety, increasing students’ confidence in self-expression, and improving the quality of their pronunciation. Key supporting factors include teacher creativity, policy support for bi’ah arabiyah, and students’ enthusiasm for learning, while interference from the Thai language and limited exposure outside of school remain obstacles that need to be addressed on an ongoing basis.